KUALITAS PERNIKAHAN DAN KESEJAHTERAAN KELUARGA MENENTUKAN KUALITAS LINGKUNGAN PENGASUHAN ANAK PADA PASANGAN YANG MENIKAH USIA MUDA - Tyas, Putri Fatma; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2017)
This study aimed to analyze the influence of family characteristics, quality of marriage, and family well-being toward the quality of parental environment among early marriage families. Research is done in two villages in Ciampea District, Bogor Regency, West Java Province. Samples consist of 70 families selected purposively with consideration of husband and wife married at a young age and have children aged 0-6 years old. Data were collected through interviews and observations and analyzed with descriptive statistics and multiple linear regressions. The analysis found that majority family had marriage quality in the medium category. Meanwhile, a majority of the family were categorized as prosperous family based on objective well-being indicator and had subjective family well-being in the medium category. This research also found that the majority of quality of parental environmental for children aged 0-36 months was categorized as low environment and children aged 37-72 months in the medium category. Marriage age, the marriageable age of wife, marriage quality, and subjective well-being significant and positive influenced toward the quality of parenting environment.